Effectiveness of therapeutic plasma exchange in a critically ill child with secondary hemophagocytic lymphohistiocytosis - Prashant Kumar Pandey (Asian Journal of Transfusion Science, 2019)
Currently, the ASFA has not included TPE in the management of HLH but many cases reports have reported successful role of TPE in HLH. Here we are presenting a case in which HLH was managed successfully with TPE. Diagnosis of HLH is based on the HLH 2004 diagnostic criteria proposed by HLH society. TPE was done using COM.TEC (Fresenius Kabi, Germany). Patient required three sessions of TPE. After three sessions of TPE patient's clinical condition improved remarkably and he was switched to IV Dexamethasone as maintenance treatment. One standard TPE procedure was 1.5 plasma volume exchanges. In view of deranged coagulation profile fresh frozen plasma was used as a replacement fluid. During follow up after one month of discharge, patient was absolutely normal. In developing countries like India, where infections are still a prime concern to the physicians, making an accurate diagnosis of HLH is a great concern. High suspicion, timely diagnosis and early start of TPE can be life saving in such patients.